ICT "Tools" to Improve Quality Assurance in Africa Educational System (Nigeria as Case Study) - Rufai, M. M. (2012)
This research paper uses the terms "tools" to include the computer hardware, software, and connectivity put together under the title Information and Communication Technology (ICT). Authors of this research work considered Indicators of declining quality and wastage in the education system to include; high drop-out and Failure rates, rampant examination malpractices, poor reading and writing skills among students at all levels. The focus of this paper is on how qualitative education can be guaranteed in African schools through the use of ICT to reduce failure rates in examinations. This research work uses the extent to which the graduates of an educational system meet the educational set goals to determine the quality assurance. Section 1 of the paper discusses the concept ICT in related to education system; Section 2, literature review discusses educational goals, and quality assurance; Section 3 discusses the research methodology as in research framework- which is based on design of computer software refers to as ³expert tutor´ system by author to teach a topic in Biology (Sense Organs) and research methodology-compared the usefulness of expert program tutors designed by the researchers and face-to-face classroom teaching; Section 4 presents finding and analyses of the results; section 5 discusses the results; Section 6 gives the conclusions based on Implication of the expert tutor design on educational practice, policy and Future research directions.